2006
DOI: 10.1111/j.1875-595x.2006.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental attendance by insurance status among adults in Tehran, Iran

Abstract: In a country with a low dentist-population rate dental attendance is positively related not only to insurance status, but also to gender and to level of education. Accordingly, dental insurance coverage should be expanded to facilitate access to dental care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 19 publications
5
29
0
Order By: Relevance
“…Since most participants had an adequate level of knowledge towards dental and oral healthcare, these results can be attributed to addiction and the influence of drug abuse on the patient's behavior, type of drug and its abuse, age, and the duration of addiction. The dental and oral health status among the methamphetamine abusers ( Table 1, Table 2) was much worse than that among the non-methamphetamine drug abusers, as reported for the general Iranian population in the previous studies [19][20][21] as well as some other investigations around the world [22,23]. The present study shows a high predominance of TMJ disorders in the methamphetamine abusers as compared to the non-methamphetamine addicts.…”
Section: Discussionsupporting
confidence: 42%
“…Since most participants had an adequate level of knowledge towards dental and oral healthcare, these results can be attributed to addiction and the influence of drug abuse on the patient's behavior, type of drug and its abuse, age, and the duration of addiction. The dental and oral health status among the methamphetamine abusers ( Table 1, Table 2) was much worse than that among the non-methamphetamine drug abusers, as reported for the general Iranian population in the previous studies [19][20][21] as well as some other investigations around the world [22,23]. The present study shows a high predominance of TMJ disorders in the methamphetamine abusers as compared to the non-methamphetamine addicts.…”
Section: Discussionsupporting
confidence: 42%
“…In this case, an RII value greater (lesser) than 1 show that dentists are more available in the provinces with higher (lower) SR. To account for effect of demographic confounders (age and gender), the adjusted RII was also calculated by including the proportion of female in the population, proportion of people younger than 15 years old and proportion of people older than 65 years old as covariates in our regression. The reason for including these covariates in the analysis was that the previous studies showed that age and gender are significantly associated with demand for dental services in the country [23,33]. …”
Section: Methodsmentioning
confidence: 99%
“…Actually, access to health care and distribution of resources within health sector is considered as one of the social determinants of health [18,19]. Although studies in Iran have examined the association between demographic and SR with population’s oral health status [20,21,22] and utilization of dental services [23], little attention has been paid to the distribution of dentists across the provinces in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Dental insurance has been reported to be associated with higher percentages visiting within the last year,23 and visiting for a check-up 21. such associations of insurance status with access to services may be expected to have an impact on the pattern of service received.…”
Section: Discussionmentioning
confidence: 99%
“…The dentist:population ratio in Tehran is 1:1,800, with about 4,500 practicing dentists serving the eight million inhabitants in the city. Details of the Iranian health insurance system have been described previously 21,23…”
Section: Methodsmentioning
confidence: 99%